2020
DOI: 10.32014/2020.2518-1467.127
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Emotional Intelligence and Academic Achievement Among Undergraduate Students in Kazakhstan

Abstract: Б а с р е д а к т о р ы х.ғ.д., проф., ҚР ҰҒА академигі М.Ж. Жұрынов Р е д а к ц и я а л қ а с ы: Абиев Р.Ш. проф. (Ресей) Абылкасымова А.Е. проф., академик (Қазақстан) Аврамов К.В. проф. (Украина) Аппель Юрген проф. (Германия) Баймуқанов Д.А. проф., академик (Қазақстан) Баймұратов У.Б. проф., академик (Қазақстан) Байтанаев Б.А. проф., академик (Қазақстан) Байтулин И.О. проф., академик (Қазақстан) Банас Иозеф проф. (Польша) Берсимбаев Р.И. проф., академик (Қазақстан) Велесько С. проф. (Германия) Велихов Е.П. п… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…However, Fahim and Pishghadam (2007) focused only on English major students, and though confirming the association between intrapersonal, stress management, and AA, presented the third associative dimension as general mood competencies rather than adaptability. In another study, Fillipova and Bilyalov (2020) found that although self-management and intrapersonal components positively correlate with and predict AA, the interpersonal component poses a negative correlation, revealing that not all aspects of EQ can be a predictor of students’ success.…”
Section: Review Of Literaturementioning
confidence: 96%
“…However, Fahim and Pishghadam (2007) focused only on English major students, and though confirming the association between intrapersonal, stress management, and AA, presented the third associative dimension as general mood competencies rather than adaptability. In another study, Fillipova and Bilyalov (2020) found that although self-management and intrapersonal components positively correlate with and predict AA, the interpersonal component poses a negative correlation, revealing that not all aspects of EQ can be a predictor of students’ success.…”
Section: Review Of Literaturementioning
confidence: 96%